2021
DOI: 10.3390/app11020805
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, Assessment and Design of an Emergency Department of a Public Hospital through Discrete-Event Simulation

Abstract: Emergency departments in hospitals are having many difficulties in achieving the performance levels required by health regulators and society. The waiting times as well as the total throughput time are examples of performance indicators that emergency departments need to improve in order to provide a better service to the community. To achieve improvement of performance, the present paper shows a methodology to assist the design process of an emergency department using simulation techniques. In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
0
15
0
3
Order By: Relevance
“…He concluded that issues in hospital were well resolved through that simulation and modifications in queueing have been done. Castanheira-Pinto et al [ 180 ] presented a methodology to assist the design process of an ED using a DES simulation technique. The ED of a hospital in Portugal was considered for testing that technique.…”
Section: Scientific Modeling Methodsmentioning
confidence: 99%
“…He concluded that issues in hospital were well resolved through that simulation and modifications in queueing have been done. Castanheira-Pinto et al [ 180 ] presented a methodology to assist the design process of an ED using a DES simulation technique. The ED of a hospital in Portugal was considered for testing that technique.…”
Section: Scientific Modeling Methodsmentioning
confidence: 99%
“…However, upon gaining the higher-level view, a detailed process model is needed for a better understanding of the intricacies on the ground. Solutions underpinned by Operations Research/Management (OR/OM) methods, including simulation techniques, have been commonly used to solve bottlenecks in the ED [23,57,[61][62][63][64]. For example, Discrete Event Simulation (DES) has been applied to model EDs at an operational level [64,65].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…O departamento de emergência tem estado sob pressão crescente, impactando diretamente a capacidade de atendimento. Além disso, tem dificuldades em atingir os níveis de desempenho exigidos pelos reguladores de saúde e pela sociedade (Castanheira-Pinto et al, 2021;Swancutt et al, 2017). Ademais, a demanda contínua e os orçamentos apertados levam alguns hospitais a apresentar baixo desempenho, impactando a satisfação do paciente (Alnajem et al, 2019).…”
Section: Emergência Hospitalarunclassified
“…No entanto, não há acordo sobre como definir metas de tempo de espera e priorizar listas de espera. Assim, os tempos de espera e o tempo total de processamento são exemplos de indicadores de desempenho que precisam ser gerenciados e reduzidos nos prontos-socorros, de forma a atender melhor a comunidade (Castanheira-Pinto et al, 2021). Para isso, a abordagem LH tem sido adotada (Swancutt et al, 2017).…”
Section: Emergência Hospitalarunclassified
See 1 more Smart Citation